MENYEBUTKAN SUMBER SUMBER HUKUM INTERNASIONAL - Vega, Niken Kuratu; Guspita, Devika Rosa; Sadiah, Naisa; Rahmawati, Lulu; Herka, Satrio Yudha Pratama; Fauzi, Akmal; Bhagaskoro, Wahyu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
International law as a system of norms that regulates relations between countries has sources that serve as the main reference in resolving disputes and upholding global justice. This study aims to identify and analyze sources of international law, including international treaties, customary international law, general legal principles, court decisions, and the doctrines of legal experts, and to examine their implementation in the Indonesian national legal system. This study is a normative legal study (normative juridical) with descriptive-analytical specifications using library research methods and legislative, conceptual, and case approaches. The results show that international treaties are the primary written and binding source based on the principle of pacta sunt servanda, but their effectiveness depends on the political will of the state and the ratification process (Bagus et al., 2025; Sutrisno, 2025). Customary international law acts as a dynamic source that fills legal gaps through consistent state practices and opinio juris (Noval Dwi Satria et al., 2025; Zaenudin et al., 2025). International court decisions and the doctrines of legal experts serve as additional sources that aid the interpretation and development of international law (Siregar et al., 2024). The implementation of international legal sources in Indonesia faces challenges such as delayed ratification, lack of legal harmonization, and poor understanding among law enforcement officials. This study recommends accelerating ratification, harmonizing national laws, and strengthening the capacity of law enforcement officials to understand international law